Evaluation of Agreement between HRT III and iVue OCT in Glaucoma and Ocular Hypertension Patients - A. Perdicchi; M. Iester; D. Iacovello; A. Cutini; M. Balestrieri; M. G. Mutolo; A. Ferreras; M. T. Contestabile; S. M. Recupero (Journal of Ophthalmology)
Purpose. To determine the agreement between Moorfields Regression Analysis (MRA), Glaucoma Probability Score (GPS) of Heidelberg retinal tomograph (HRT III), and peripapillary nerve fibers thickness by iVue Optical Coherence Tomography (OCT). Methods. 72 eyes with ocular hypertension or primary open angle glaucoma (POAG) were included in the study: 54 eyes had normal visual fields (VF) and 18 had VF damage. All subjects performed achromatic 30° VF by Octopus Program G1X dynamic strategy and were imaged with HRT III and iVue OCT. Sectorial and global MRA, GPS, and OCT parameters were used for the analysis. Kappa statistic was used to assess the agreement between methods. Results. A significant agreement between iVue OCT and GPS for the inferotemporal quadrant (κ: 0.555) was found in patients with abnormal VF. A good overall agreement between GPS and MRA was found in all the eyes tested (κ: 0.511). A good agreement between iVue OCT and MRA was shown in the superonasal (κ: 0.656) and nasal (κ: 0.627) quadrants followed by the superotemporal (κ: 0.602) and inferotemporal (κ: 0.586) sectors in all the studied eyes. Conclusion. The highest percentages of agreement were found per quadrant of the MRA and the iVue OCT confirming that in glaucoma damage starts from the temporal hemiretina.